3B.06: CARDIOVASCULAR RISK IN PEDIATRIC RECIPIENTS OF STEM CELL TRANSPLANTATION. (June 2015) - Schmidt, B.; Thurn-Valsassina, D.; Beier, R.; Melk, A.
Abstract : Objective: Different from recipients of a solid organ transplant, stem cell transplantation (SCT) recipients do not receive long term immunosuppressive treatment that may cause renal and cardiovascular damage. Despite this fact, adult SCT recipients have been shown to be at increased cardiovascular risk supposedly due to cardiotoxic conditioning treatment. We analyzed blood pressure (BP) and markers of cardiovascular risk in pediatric SCT recipients. Design and method: We have currently investigated 41 pediatric recipients of allogeneic SCT. Patients were 6–25 years old and had been transplanted between 3 months to 10 years ago. We assessed casual BP, aortal pulse wave velocity (PWV) and carotid intima-media thickness (IMT). In 32 patients, we also performed ambulatory BP measurements (ABPM). All values were normalized for age and expressed as SDS values. Results: None of the patients was hypertensive (> 95. percentile for gender, age, height) based on casual BP measurements at time of the investigation; with two patients receiving antihypertensive therapy. However, hypertension was discovered in 6 patients by ABPM. Mean PWV was 0.2 ± 1.09 SDS adjusted for age; 1 patient showed PWV values elevated > 95. percentile. Mean IMT was 1.64 ± 1.00 SDS adjusted for age; 8 patients (47%) showed IMT values > 95. percentile. Conclusions: Pediatric SCT recipients showed a high incidence of masked hypertension, i.e. hypertension detected only by ABPM in presence of normal casual BP values. The cardiovascular risk induced by masked hypertension is similar to the risk seen with true hypertension (detected also by casual BP). Accordingly, IMT reflecting atherosclerotic changes was prominent in these patients. In conclusion, ABPM should be performed routinely in SCT recipients to detect masked hypertension.